2002
DOI: 10.1016/s0925-4773(01)00653-0
|View full text |Cite
|
Sign up to set email alerts
|

Gbx2 interacts with Otx2 and patterns the anterior–posterior axis during gastrulation in Xenopus

Abstract: Anterior-posterior patterning of the embryo requires the activity of multiple homeobox genes among them Hox, caudal (Cdx, Xcad) and Otx2. During early gastrulation, Otx2 and Xcad2 establish a cross-regulatory network, which is an early event in the anterior-posterior patterning of the embryo. As gastrulation proceeds and the embryo elongates, a new domain forms, which expresses neither, Otx2 nor Xcad2 genes. Early transcription of the Xenopus Gbx2 homologue, Xgbx2a, is spatially restricted between Otx2 and Xca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
32
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 70 publications
4
32
0
Order By: Relevance
“…In frogs, Otx has been shown to negatively regulate convergent extension movements through Calponin (34). A subdivision into an anterior otx-and a posteriorly adjacent gbx-expressing region is of widespread occurrence in developing bilaterians (1,(35)(36)(37)(38), but a spatial correlation to the anteroposterior extent of convergent extension has not been documented except for vertebrates.…”
Section: An Otx-gbx Morphogenetic Boundary Anteriorly Delimitates Thementioning
confidence: 99%
“…In frogs, Otx has been shown to negatively regulate convergent extension movements through Calponin (34). A subdivision into an anterior otx-and a posteriorly adjacent gbx-expressing region is of widespread occurrence in developing bilaterians (1,(35)(36)(37)(38), but a spatial correlation to the anteroposterior extent of convergent extension has not been documented except for vertebrates.…”
Section: An Otx-gbx Morphogenetic Boundary Anteriorly Delimitates Thementioning
confidence: 99%
“…In addition, gain-of-function experiments showed that mis-expression of Gbx2 in the midbrain causes repression of Otx2 and anterior expansion of r1 (Katahira et al, 2000;Kikuta et al, 2003;Millet et al, 1999;Tour et al, 2002), and that this is dependent on the repressor function of Gbx2 (Tour et al, 2002). However, Gbx2 also has been shown to function as a transcriptional activator in certain cellular contexts (Kowenz-Leutz et al, 1997).…”
Section: Gbx2 Is Not Sufficient To Induce a Cerebellummentioning
confidence: 99%
“…In vertebrates, both Fgf8 and Gbx2 have a repressive activity on Otx2 expression in the metencephalic alar plate (Liu and Joyner, 1999;Martinez et al, 1999;Millet et al, 1999;Tour et al, 2002). In addition, zebrafish gbx2 is fully dependent on Fgf8 during the maintenance period (Rhinn et al, 2003).…”
Section: Possible Molecular Mechanisms Underlying the Isthmus-to-midbmentioning
confidence: 99%